Integrating Oral History and Archaeology of the 1845 Franklin Expedition: The Case From Kungearkbeearu - Stenton, Douglas R.; Park, Robert W. (The Arctic Institute of North America, 2024)
Attempts to accurately reconstruct events that occurred during the final phases of the 1845 Franklin Northwest Passage expedition face a key challenge: how to address inconsistencies and, in some cases, contradictions between historical descriptions of sites and the archaeological evidence they contain. This paper examines the case of site NcLa-1 at Kungearkbeearu, on the Simpson Strait coast of King William Island, for which the Inuit oral history seems incompatible with archaeological interpretations. New archaeological data from the site provide an enhanced framework within which to evaluate both the oral history and archaeology of NcLa-1. Les tentatives de reconstruction précise des événements qui se sont produits pendant les dernières étapes de l’expédition de Franklin dans le passage du Nord-Ouest en 1845 font face à un important défi, c’est-à-dire comment résoudre les incohérences et, dans certains cas, les contradictions entre les descriptions historiques des sites et les preuves archéologiques qu’ils renferment. Cet article examine le cas du site NcLa-1 à Kungearkbeearu, sur la côte de l’île King William dans le détroit de Simpson, pour lequel l’histoire orale inuite semble incompatible avec les interprétations archéologiques. De nouvelles données archéologiques provenant du site ont donné lieu à un cadre de référence amélioré pour évaluer tant l’histoire orale que l’archéologie de NcLa-1.